Upregulation of XIAP promotes lung adenocarcinoma brain metastasis by modulating ceRNA network - Wang, Yingjing; Shen, Lu; Li, Geng; Chen, Jiayi; Ge, Rong (Frontiers in Oncology, 2022)
Brain metastasis is reportedly the principal cause of lung-cancer-related deaths, which associated with poor prognosis and recurrence. However, the function and mechanisms of XIAP in lung adenocarcinoma with brain metastasis (LUAD-BM) remains poorly understood. In this study, we analyzed the differential mRNA of 58 lung adenocarcinomas samples and 28 lung adenocarcinomas with brain metastases in GEO database. 191 differentially expressed mRNAs were significantly associated with immune response, the proliferation of the immune cell, cell-cell adhesion. Subsequent analyzed by lasso and SVM found that XIAP was significantly elevated in LUAD-BM and significantly associated with LUAD grade and metastasis. Then we constructed the SBF2-AS1/RUNDC3A-AS1–has-miR-338-3p–XIAP network by Cystoscope based on the correlation obtained from Starbase. Specifically, XIAP was closely correlation with T cells, B cells, Mast cells, macrophages, and dendritic cells. In conclusion, we found that upregulated of XIAP could associated with LUAD-BM and immune infiltration. And the brain metastasis process may be achieved by regulating the SBF2-AS1 or RUNDC3A-AS1 and has-miR-338-3p axis.